Needs analysis for developing teacher leadership based gamified teaching materials to foster mental resilience in remote schools - Mahin Ainun Naim; Sahrul Muzakki; Mutmainnah; Ja’far Shodiq (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to identify the needs for developing teacher leadership–based gamified teaching materials to strengthen students’ mental resilience in remote school settings. Employing a Research and Development (R&D) approach using the ADDIE model, the study focuses on the analysis phase as a preliminary investigation. A qualitative descriptive design was used, with data collected through classroom observations, analysis of instructional documents, and semi-structured interviews with teachers and students in five junior high schools in remote areas of Madura. The findings indicate that learning practices remain predominantly conventional and text-based, offering limited opportunities to foster student engagement and mental resilience. Although instructional documents meet curriculum standards, they lack visual, progressive, and challenge-oriented activities. Both teachers and students express a strong need for interactive learning media that support teacher leadership while enhancing students’ confidence, persistence, and psychological safety. These results highlight a significant gap between current instructional practices and the pedagogical requirements for developing students’ mental resilience, providing a strong foundation for the development of context-appropriate gamified teaching materials for remote schools.